Determining Competencies for Frontline Sales Managers in For-Profit Organizations. (August 2013) - Busch, Tina K.
The Problem: With sales models evolving in response to the changing marketplace, knowing the skills required for sales effectiveness is key to organizational competitive advantage. Frontline sales managers are the most critical role in a productive sales force; however, empirical research focusing on sales manager competence is limited. The Solution: Understanding the knowledge and skills necessary for success as a frontline sales manager can assist in improving individual, team, and organizational sales performance. This article adds to the knowledge base by providing a frontline sales manager competency model that can serve as a guide for human resources initiatives to increase sales force effectiveness and help bridge the gap between theory and practice. The Stakeholders: Competency models are valuable across industries, and human resources professionals, senior leaders, sales organizations, and researchers can learn from the findings of this study and adapt them to their context.